Reviews. Issue 1 (1st March 2019) - Tao, Yu; Ma, Xiao
Mapping the New African Diaspora in China: Race and The Cultural Politics Of Belonging, Shanshan Lan (2017) New York and London: Routledge, 202 pp., ISBN 978-1-13867-306-9, h/bk, £105International Migrants in China's Global City: The New Shanghailanders, James Farrer (2019) Oxon and New York: Routledge, 216 pp, ISBN 978-0-81538-263-8, h/bk, 140